Ethanolic extract of Parkia speciosa Hassk leaves innovation of gastroretentive tablet: standardization and optimization - Nurfitriyana Nurfitriyana; Fitriya Fitriya; Najma Annuria Fithri; Dwi Kurnia Putri; Siti Marwah Lestari; Dyah Ayuwati Waluyo; Hardiyanti Syarif (Faculty of Pharmacy, Universitas Pancasila, 2025)
Parkia speciosa ethanol leaves extract contains flavonoid, tannin, and terpen as ulcus peptic remedy. These compounds exhibit limited activity in the stomach due to the short gastric residence time following oral administration. The formulation of gastroretentive tablets can overcome this limitation. This research aims to control the prolonged release of drugs in the stomach to increase bioavailability and characterize the ethanol leaves extract. Extraction was carried out by maceration using ethanol, followed by standardization based on specific and non-specific parameters extract. Gastroretentive tablet was formulated with combination of HPMC-K4M and chitosan using factorial design 22. Effects of compositional factors and their interactions on gastroretentive tablet was observed on hardness, friability, floating lag/duration time, swelling index, and mucoadhesive time. Results standardization extract showed that extract met the required criteria for both specific parameters (organoleptic properties and phytochemical screening) and non-specific parameters (moisture content, loss on drying, water/ethanol-soluble extract content). Based on with DX®10 analysis, the optimum formulation was achieved with 20.25% of HPMC-K4M and 10.26% of chitosan. The analysis of the optimum formulation characteristics was as follows: friability (0.22%), hardness (29.53 N), mucoadhesive time (22.86 hours), floating lag/duration time (27.54 minutes; 12 hours), and swelling index (312.82%). Result revealed that gastroretentive tablets formulated with ethanol extract of Parkia speciosa leaves improve gastric residence duration and promote better bioavailability.